2022
DOI: 10.3390/polym14071281
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Aminomethacrylate-Based Copolymer for Solubility Enhancement—From Radical Polymer Synthesis to Manufacture and Characterization of Amorphous Solid Dispersions

Abstract: The present study covers the synthesis, purification and evaluation of a novel aminomethacrylate-based copolymer in terms of its suitability for improving the solubility and in vitro release of poorly water-soluble drug compounds. The new copolymer was synthesized by solvent polymerization with radical initiation and by use of a chain transfer agent. Based on its composition, it can be considered as a modified type of dimethylaminoethyl methacrylate-butyl methacrylate-methyl methacrylate “EUDRAGIT® E PO” (ModE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Concluding from these observations on the release performance obtained when E-173 kDa was used in the S-SNEDDS technology, it can be assumed that the higher flexibility of the polymer chains in the E-173 kDa copolymer resulted in good solubilization of the drugs celecoxib, efavirenz, and fenofibrate, respectively. As already stated, the trend regarding an improved drug release performance of S-SNEDDS containing ModE with lower M w observed in the present study was in good agreement with that observed in a previous study [22]. In both studies, the drug release of celecoxib-, efavirenz-and fenofibrate formulations with the same drug dose was investigated.…”
Section: Dissolution Studiessupporting
confidence: 92%
See 4 more Smart Citations
“…Concluding from these observations on the release performance obtained when E-173 kDa was used in the S-SNEDDS technology, it can be assumed that the higher flexibility of the polymer chains in the E-173 kDa copolymer resulted in good solubilization of the drugs celecoxib, efavirenz, and fenofibrate, respectively. As already stated, the trend regarding an improved drug release performance of S-SNEDDS containing ModE with lower M w observed in the present study was in good agreement with that observed in a previous study [22]. In both studies, the drug release of celecoxib-, efavirenz-and fenofibrate formulations with the same drug dose was investigated.…”
Section: Dissolution Studiessupporting
confidence: 92%
“…A comparison of the rate and extent of drug release of the S-SNEDDS prepared from different ModE types showed that a higher M w or a higher T g of the ModE copolymer used resulted in a decrease, both in the rate and extent of celecoxib-, efavirenz-, and fenofibrate release within the test period of 120 min (Figures 1a, 2a and 3a). These observations correlate with those made when ModE was used in the preparation of ASD [22]. The observed effect of M w and T g on drug release performance (dissolution rate of the drug substance was inversely proportional with M w and T g of a copolymer) was also determined by Knopp et al [25], who studied polyvinylpyrrolidone-based ASDs incorporating the drug substance celecoxib.…”
Section: Dissolution Studiessupporting
confidence: 78%
See 3 more Smart Citations